Pengaruh Literasi Keuangan Dan Locus Of Control Terhadap Keputusan Investasi: Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Makassar - Nurjannah Tawakkal; Muhammad Nur Abdi; Masrullah Masrullah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of financial literacy and locus of control on the investment decisions of students at the faculty of economics and business, Universitas Muhammadiyah Makassar. This research employs a quantitative approach, with data collected through questionnaires distributed to 96 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS 26 software. The results of the study indicate that financial literacy has a positive and significant effect on investment decisions. Likewise, locus of control also has a positive and significant effect on investment decisions. These findings suggest that the higher the level of financial literacy and locus of control possessed by students, the wiser they are in making investment decisions.